Egypt's Post-Arab Spring Revolution Explanation for Democratisation Failure - Jamilah, Maryam; Nanda, Bima Jon (Jurnal Demokrasi dan Politik Lokal, 2024)
The Arab Spring phenomena fueled international confidence in the Middle East's democratization process. The democratic election of Muhammad Morsi (Muslim Brotherhood) as President of Egypt was one of the Arab Spring Revolution's most significant victories. However, on July 3, 2013, General Abdul Fattah Al-Sisi, the Head of Egypt's Armed Forces, conducted a coup to topple Morsi's rule. That action is incompatible with democratic principles. The failure of this democratization process is the primary subject of this research. The purpose of this article is to understand the contributing causes to Egypt's democratization failure following the Arab Spring movement of 201. The author explains the phenomena using a qualitative technique with Miles and Huberman's descriptive-analysis methodology, as well as three theories: Seymour Lipset's modernization theory, Huntington's political actor theory, and Philip C. Schmitter's international environment theory. This report discovered that three causes contributed to Egypt's democratization failure: a lack of economic conditions, a relationship between the MB (Muslim Brotherhood) and Salafis, a lack of international backing, and GCC state meddling.